How Much Additional Information Is Provided by High‐Frequency‐Audiometry in Tinnitus Patients with Normal Standard Audiogram?. (23rd August 2013) - Kleinjung, Tobias; Lehner, Astrid; Fiedler, Isabella; Steffens, Thomas; Strutz, Jurgen; Langguth, Berthold; Vielsmeier, Veronika
Abstract : Objectives: The majority of tinnitus patients suffer from hearing loss. However, a significant proportion of tinnitus patients show normal hearing thresholds in the standard pure tone audiogram (PTA, 125Hz – 8kHz). It has been argued that PTA is not sensitive for all forms of hearing impairment and the additional measurement of high frequencies (9 – 16 kHz) should complete the diagnostic set‐up. Here we aimed to investigate whether the results of high frequency audiometry (HFA) provide relevant additional information in tinnitus patients with normal standard PTA. Methods: From the database of the Tinnitus Clinic of the University of Regensburg we identified 75 patients with normal hearing thresholds in the standard PTA. We then contrasted patients with normal and pathological HFA and compared these two groups with respect to tinnitus severity, laterality, duration, tinnitus pitch, the presentation of selected somatic symptoms, and triggers of tinnitus onset. Results: Patients with pathological HFA were significantly older and had higher scores on the Tinnitus Questionnaire and the Tinnitus Handicap Inventory in comparison to patients with normal HFA. Furthermore, there was an association of high frequency audiograms and the laterality of tinnitus: patients with left and bilateral tinnitus had more pronounced high frequency hearing loss in the left ear. Conclusions: In summary, our data indicate that in patients with normal hearing in standard PTA, some additional information is provided by HFA. The association between tinnitus laterality and asymmetry of HFA suggests a potential causal role for the high frequency hearing loss in tinnitus etiopathogenesis.